2018
DOI: 10.1055/a-0633-1720
|View full text |Cite
|
Sign up to set email alerts
|

Ramadan Observance during Pregnancy in Germany: a Challenge for Prenatal Care

Abstract: Introduction Fasting during Ramadan while pregnant has been shown to have long-term negative effects on the offspringʼs physical and cognitive health. Even though most Muslims do not believe pregnant women are obligated to fast during Ramadan, fasting rates of up to 87% have been reported for pregnant women. No data exists to date about Ramadan adherence and behavior in Germany. Methods The Mainz Study of Ramadan and Pregnancy surveyed pregnant Muslims and new Muslim mothers in Mainz between October 2016 and J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…To our knowledge, this is one of the first studies that examined the characteristics and outcomes of Ramadan fasting in pregnant women over a period of 10 years since most of the studies were conducted over one or few years. 5,8,[10][11][12][13][14][15] The rate of fasting in the current study (84.9%) was similar to the rate of a study conducted in Pakistan (82.8%) and another in Indonesia (80%). 5,13 Other studies showed a lower prevalence of fasting.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…To our knowledge, this is one of the first studies that examined the characteristics and outcomes of Ramadan fasting in pregnant women over a period of 10 years since most of the studies were conducted over one or few years. 5,8,[10][11][12][13][14][15] The rate of fasting in the current study (84.9%) was similar to the rate of a study conducted in Pakistan (82.8%) and another in Indonesia (80%). 5,13 Other studies showed a lower prevalence of fasting.…”
Section: Resultssupporting
confidence: 86%
“…11 Similarly, the prevalence of fasting was 53.9% in a study done in Netherlands and 43% in a German study. 6,15 In the current study, of those who fasted, 65.3% fasted more than 15 days while the rate in Netherlands study was 37.7% and that of Iraq was around 85%. 6,14 The rate of adherence to fasting could be reflected in how the women perceive the religious rule of fasting in pregnancy or how their healthcare providers failed to give them relevant information.…”
Section: Resultsmentioning
confidence: 48%
See 1 more Smart Citation
“…For all these reasons, Muslim women might prefer to fast during Ramadan even when pregnant. Previously reported proportions of pregnant women who fast at least on some days during Ramadan range from around 50% in some high-income countries (Leimer, Pradella, Fruth, Queisser, & van Ewijk, 2018;Savitri et al, 2014) and around 60% in Iran (Ziaee et al, 2010) and Iraq (Safari, Piro, & Ahmad, 2019) to up to 80-90% in the Gambia (Prentice, Prentice, Lamb, Lunn, & Austin, 1983), Indonesia (Savitri et al, 2018), Pakistan (Mubeen, Mansoor, Hussain, & Qadir, 2012) and Yemen (Makki, 2002). Adherence to Ramadan fasting during pregnancy in the present study was comparable to the high levels reported in other low-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…Following Ramadan in 2018, all pregnant Muslim women and a random third of non-pregnant Muslim women in the FAARM trial were interviewed about their fasting practices and beliefs (n = 852). We adapted a questionnaire from a previous study in Germany (Leimer, Pradella, Fruth, Queisser, & van Ewijk, 2018) to our study setting (available in the supporting information, Table S1).…”
Section: Data Collectionmentioning
confidence: 99%